The influence of 5-iron clubhead mass distribution on clubhead presentation and initial ball launch conditions: Part I: Golf robot tests - Wallace, E. S.; Corke, T. W.; Jones, K. M.; Betzler, N. F.; Otto, S. R. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
It is well accepted that iron clubhead properties affect shot outcomes in golf. However, the mechanisms that contribute to this relationship have not received recent scientific study. The purpose of this study was to determine how the different clubhead mass distributions in a blade 5-iron and a cavity-back 5-iron affect clubhead presentation and ball launch conditions. Nine clubhead presentation variables and four ball launch variables were measured for ten discrete impact locations and five face angles during swings using a golf robot. Group means were analysed statistically using an independent samples approach to identify differences and linear regression was used to indicate relationships between key launch variables. The cavity-back showed higher effective clubhead loft with greater total ball spin than the blade, despite having matched static lofts, whilst also providing more consistent launch outcomes across a range of impact locations. Evidence of the phenomenon known as the `gear effect` was found for the cavity-back, but not the blade, suggesting that the threshold at which the clubhead`s centre of gravity (CG) is deep enough to detect the gear effect lies between the CGs of the two 5-iron types. These novel robot test findings lend support to the perceived performance benefits of perimeter-weighted irons; whether these effects translate to human golfer swings is reported in Part II of this paper.